Pengembangan Materi Pendidikan Agama Islam Berbasis Rumah - Suhardin Suhardin; Hayadin Hayadin; Sugiarti Sugiarti; Ani Marlina (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2021)
Abstract This article aims to discuss the development of Islamic religious education materials available for parents at home. The significance of home-based materials was motivated by the paralysis of the school's function in serving the learning process, including children's religious education, when the COVID-19 outbreak hit the world. This article comes from research and development involving education stakeholders, especially teachers, supervisors, and parents. The activities in focus group discussions were carried out in three places, namely in Bandung, Serpong, and Surabaya. Awareness of the importance of minimal material for parents at home to teach and educate their children about Islam is one of the reasons why this research was conducted. The main question is, what is the minimum content of Islamic religious education that parents should teach at home. After going through a series of discussions at three workshop locations, it was concluded that the material for Islamic religious education at home should be more straightforward and complementary to the subject matter of Islamic religion at school. The materials include the creed of monotheism, aqidah (theology), which discusses Allah SWT; worship (ritual) includes prayer, fasting; muamalat, which includes the introduction of buying and selling and transactions in Islam; and morality. Â  Abstrak Artikel ini bertujuan untuk mendiskusikan pengembangan materi minimal pendidikan agama Islam yang dapat digunakan oleh orang tua dan pendidik di rumah. Ini dilatarbelakangi oleh lumpuhnya fungsi sekolah dalam melayani proses pembelajaran termasuk pembelajaran pendidikan agama anak saat wabah covid-19 melanda dunia. Artikel ini berasal dari riset dan pengembangan yang melibatkan stake-holders pendidikan khususnya guru pendidikan agama Islam, pengawas pendidikan agama Islam, dan orang tua. Kegiatan pengembangan berbentuk fokus grup diskusi dilakukan pada tiga tempat yakni di kota Bandung, kota Serpong dan kota Surabaya. Kesadaran tentang pentingnya materi minimal bagi para orang tua di rumah untuk mengajar dan mendidik anaknya tentang agama Islam menjadi salah satu alasan mengapa riset ini dilakukan. Pertanyaan utamanya adalah, apa konten minimal pendidikan agama Islam yang harus diajarkan oleh orang tua di rumah. Setelah melewati serangkaian diskusi pada tiga lokasi workhop, disimpulkan bahwa materi pendidikan agama Islam di rumah mesti lebih sederhana, dan bersifat komplementer dengan materi pelajaran agama Islam di sekolah. Materi tersebut meliputi: akidah tauhid, aqidahÂ  (teologi) yang membahas tentang Allah SWT; peribadatan (ritual) mencakup Shalat, puasa, doa-doa; muamalat yang meliputi pengenalan jual beli dan transaksi dalam Islam; dan akhlaq.